The Institutonal and Legal Guarantees of Freedom of Thought, Conscience and Religion in the Constitution of the RA - Danielyan , G. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The constitutional provisions of freedom of thought, conscience and religion are generally envisaged in the articles 17, 18 and 41 of the Constitution of the Republic of Armenia. These articles contain innovations, which mostly differ from the previous legal regulations. In order to implement the institutional and procedural guarantees of the mentioned freedom, draft laws have been elaborated and put into circulation by the Government of the Republic of Armenia. The analysis of the draft laws mentioned revealed their incompatibilities with the constitutional requirements at the conceptual level and as a result of the analysis the author suggested some scientific-practical provisions. This article touches upon some contemporary questions, such as constitutional status of religious organizations, essence of the term «national church», framework and legal basis of the relations between the state and Armenian Holy Apostolic Church, the essence of constitutional limitations on freedom of thought, conscience and religion e.t.c. The presented conclusions may be helpful in the improvement of the legislative process.
Keywords: freedom of thought, conscience and religion, Armenian Apostolic Church, religious organization, national organization, state religion, creed, religious doctrine, traditional church